2020
DOI: 10.15252/embj.2019104202
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of the IL ‐17 receptor signalosome reveals a robust regulatory feedback loop

Abstract: IL‐17 mediates immune protection from fungi and bacteria, as well as it promotes autoimmune pathologies. However, the regulation of the signal transduction from the IL‐17 receptor (IL‐17R) remained elusive. We developed a novel mass spectrometry‐based approach to identify components of the IL‐17R complex followed by analysis of their roles using reverse genetics. Besides the identification of linear ubiquitin chain assembly complex (LUBAC) as an important signal transducing component of IL‐17R, we established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 93 publications
(166 reference statements)
0
17
0
Order By: Relevance
“…One possibility is that HOIL1 plays a cell-intrinsic role in regulating ILC2, and this would be consistent with a requirement for HOIL1 in radiation-resistant, non-bone marrow-derived cells, since some ILC2 are thought to self-renew in tissues 40 . A recent study identified LUBAC as a component of the IL17RA/IL17RC receptor signaling complex (RSC) required for efficient signal transduction and NFκB activation 41 . The same study identified a negative feedback loop for the IL-17RSC, although LUBAC did not appear to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that HOIL1 plays a cell-intrinsic role in regulating ILC2, and this would be consistent with a requirement for HOIL1 in radiation-resistant, non-bone marrow-derived cells, since some ILC2 are thought to self-renew in tissues 40 . A recent study identified LUBAC as a component of the IL17RA/IL17RC receptor signaling complex (RSC) required for efficient signal transduction and NFκB activation 41 . The same study identified a negative feedback loop for the IL-17RSC, although LUBAC did not appear to be involved.…”
Section: Discussionmentioning
confidence: 99%
“…The microglia are a subtype of glial-immune sentinel cells in retina and highly express receptor for IL-17 in STZ-injected or OIR mice. Among the five receptors for IL-17 (IL17RA to IL-17RE), IL-17 has been shown to bind IL-17RA with high affinity and IL-17RA receptor has been shown to associate with other receptor such as IL-17RC, forming a IL-17R complex (Draberova et al, 2020). In the retina, IL-17RA and IL-17RC could be found to express on microglia, Muller cells, and astrocytes (Ke et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Act1 controls both the transcriptional as well as the post-transcriptional regulation of IL-17 responsive genes, by recruiting and activating different TRAF proteins (TRAF6, TRAF2), and also by directly interacting with RNAs ( Li et al, 2019 ). According to a recent study, the IL-17A/IL-17RA/IL-17RC heterotrimeric receptor recruits approximately six ACT1 molecules, which provide high-avidity docking sites for TRAF6 homotrimers ( Draberova et al, 2020 ). Non-degradative K63-linked polyubiquitination of TRAF6 by Act1 leads to the recruitment of downstream adaptor (ABIN1, TAX1BP1, TANK, NAP1), effector (TAK1, LUBAC, NEMO/IKKα/IKKβ), and regulatory proteins (IKKε, TBK1, A20, Cullin1, β-TrCP1/2) and ultimately to the activation of the NF-κB and MAP kinase pathways ( Amatya et al, 2017 ; Li et al, 2019 ; Draberova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%